2007
DOI: 10.1007/s11033-007-9160-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of a heat shock protein (Hsp90) gene from black tiger shrimp (Penaeus monodon)

Abstract: The techniques of homology cloning and anchored PCR were used to clone the Hsp90 gene from black tiger shrimp. The full length cDNA of black tiger shrimp Hsp90 (btsHsp90) contained a 5' untranslated region (UTR) of 72 bp, an ORF (open reading frame) of 2160 bp encoding a polypeptide of 720 amino acids with an estimated molecular mass of 83-kDa and a 3' UTR of 288 bp. The sequence of the coding region showed 90 and 84% homology with that of the Chiromantes haematocheir and Homo sapiens, respectively. Conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 33 publications
7
30
0
Order By: Relevance
“…But, the knowledge of its functions in crustacean is poor. We first found that KK-42 can increase shrimp (P. vannumei) survival rate [10,11]. The present study further demonstrates that the HSP90 expression is obviously induced by KK-42 in hepatopancreas of the shrimp P. vannumei (Fig.…”
Section: Phylogenetic Analysis Of the Hsp90supporting
confidence: 70%
See 1 more Smart Citation
“…But, the knowledge of its functions in crustacean is poor. We first found that KK-42 can increase shrimp (P. vannumei) survival rate [10,11]. The present study further demonstrates that the HSP90 expression is obviously induced by KK-42 in hepatopancreas of the shrimp P. vannumei (Fig.…”
Section: Phylogenetic Analysis Of the Hsp90supporting
confidence: 70%
“…Thus, a better understanding of the relationship between tolerance mechanisms against environmental stress and HSP90 expression may give rise to the possibility of more efficient control of mortality [6,7]. Up to the present, only little gene information regarding HSP90s has been obtained, including the marine crab P. trituberculatus [8], the prawns Metapenaeus ensis [9] and P. monodon [10]. The white shrimp Penaeus vannumei, an important economical species, is extensively reared in many countries.…”
mentioning
confidence: 99%
“…HSP90β lacks the glutamine-rich sequence (QTQDQ) at the N-terminus and is larger than HSP90α, whereas they exhibit different molecular chaperone functions (Lees-Miller and Anderson, 1989). The studies on HSP90 have shown that the expression of HSP90β is inducible and can be regulated by all kinds of environmental stresses, such as heat shock (Farcy et al, 2007;Jiang et al, 2009), bacterial challenge (Wei et al, 2013), and heavy metals (Ivanina et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While most of the Hsp genes are well characterized in model organisms such as Drosophila melanogaster [31][32][33] very little information is available in the case of Litopenaeus vannamei. Although several families of the Hsp genes have been identified, only full length cDNAs of Hsp21, Hsp70 and Hsp90 were characterized in Litopenaeus vannamei [34][35][36]. The extensive studies of the three major families of the heat shock proteins in model organisms demonstrate that Hsp70 has a primary role in assisting folding of nascent polypeptide chains and facilitating in repairing or degradation of damaged proteins [9].…”
Section: Discussionmentioning
confidence: 99%